A narrative review of Diabetes mellitus: An update for dentists - Alaa AL-Haddad; Yazan Hassona; Alia Silawi; Awni Al Kayed (Wolters Kluwer Medknow Publications, 2021)
Introduction: Diabetes mellitus (DM) is a common metabolic disorder and a leading cause of mortality and morbidity worldwide. Dentists are increasingly encountered with patients affected by this chronic condition. Aim: To a review on updates in DM, dental management and emergencies. Methods: Database search was carried out in PubMed and Google scholar limited to articles of English language from 1998 to 2021 and pertaining to the keywords diabetes, orofacial manifestations , dental management diabetic emergency. A narrative review of this search is presented in this article. Results and Discussion: This article gives a concise update on DM and discuss the management of diabetic patients in a dental setting. Conclusion: Discussion of the possible orofacial manifestations of DM and management of diabetic emergencies is emphasized for efficicient dental practice.